Metode Pendidikan Islam dalam Novel Amelia Serial Anak-Anak Mamak Karya Tere Liye - Lutfi Kusuma Dewi (Fakultas Agama Islam, 2015)
Metode Pendidikan Islam dalam Novel Amelia Serial Anak-Anak Mamak Karya Tere Liye